2015
DOI: 10.5596/c15-008
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Survey to Benchmark Canadian Health Facility Libraries

Abstract: <p><strong>Introduction:</strong> A benchmarking survey of Canadian health facility libraries was conducted to provide statistical data to support health librarians in the  anagement of their libraries. The objectives were to determine the status of<br />hospital libraries in Canada and to evaluate whether libraries meet the 2006 CHLA/ABSC Standards for Library and Information Services in Canadian Healthcare Facilities.</p><p><strong>Methods:</strong> An online s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It was also unexpected to learn that some hospital librarians are not providing specific educational programs or tutorials for researchers. A recent benchmark survey of Canadian health facility libraries found that 29% of librarians reported a decrease in library budgets and 36% reported their budget had stayed the same over the past 5 years [12]. Under this kind of budget constraint, we were surprised to find that 5 respondants reported that they had all the databases or resources they needed to support research.…”
Section: Discussionmentioning
confidence: 95%
“…It was also unexpected to learn that some hospital librarians are not providing specific educational programs or tutorials for researchers. A recent benchmark survey of Canadian health facility libraries found that 29% of librarians reported a decrease in library budgets and 36% reported their budget had stayed the same over the past 5 years [12]. Under this kind of budget constraint, we were surprised to find that 5 respondants reported that they had all the databases or resources they needed to support research.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier, Ducas, Demczuk, and Macdonald (2015) benchmarked Canadian health libraries against the 2006 Canadian Health Libraries Association/Association des bibliothèques de la santé du Canada Standards for Libraries and Information Services in Canadian Healthcare Facilities. Almost one-third of the 168 responses noted shortcomings in staffing compared to the level set in the Standards.…”
Section: Benchmark Surveysmentioning
confidence: 99%
“…Respondents indicated that they provide a range of services, including clinical or embedded librarian services, teaching and involvement in research teams. The authors noted: ‘The provision of what formerly may have been enhanced services is increasingly the new normal for health facility libraries’ …”
Section: Significant Trends: 2010–2020mentioning
confidence: 99%
“…In the 2013 CHLA/ABSC survey, respondents identified library funding and the ability to demonstrate value as two key issues facing their organisations . The 2015 benchmarking survey of Canadian health facility libraries found that most are using some form of service evaluation, ranging from formal user consultation to key performance indicators . However, the authors noted that given organisations' increasing emphasis on accountability there is room for improvement.…”
Section: Significant Trends: 2010–2020mentioning
confidence: 99%
See 1 more Smart Citation